2015
DOI: 10.1002/nav.21615
|View full text |Cite
|
Sign up to set email alerts
|

Proportionate flow shop: New complexity results and models with due date assignment

Abstract: Abstract:It is known that the proportionate flow shop minimum makespan F m/prpt/C max problem is solved optimally by any permutation job sequence. We show that the F m/prpt/C max problem is at least ordinary NP-hard when missing operations are allowed and present some solvable cases. We then consider the standard proportionate flow shop problem (with no missing operations) and show that the solution algorithms for a class of single-machine due date assignment problems can be extended/generalized to the corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…140). The extension of the optimal 1 / / CD and 1 / / DD sequences to the proportionate flow shop was recently shown by Panwalkar and Koulamas . To the best of our knowledge, all other results mentioned above (including the modifications of some of these results as outlined in Baker and Scudder and in Gordon et al ) have not been shown to extend to the proportionate flow shop.…”
Section: Problems With Fixed Job Processing Timesmentioning
confidence: 77%
See 3 more Smart Citations
“…140). The extension of the optimal 1 / / CD and 1 / / DD sequences to the proportionate flow shop was recently shown by Panwalkar and Koulamas . To the best of our knowledge, all other results mentioned above (including the modifications of some of these results as outlined in Baker and Scudder and in Gordon et al ) have not been shown to extend to the proportionate flow shop.…”
Section: Problems With Fixed Job Processing Timesmentioning
confidence: 77%
“…Let [j ] denote the job in the j th position in the sequence and I [j ] denote the idle time on the last machine immediately preceding job [j ]; by assumption, p [0] = 0. Then, as shown in Panwalkar and Koulamas [31],…”
Section: Sufficient Conditions For the Extension Of A Single-machine mentioning
confidence: 85%
See 2 more Smart Citations